Pendampingan Guru dalam Penyusunan RPPH Berbasis Kurikulum Merdeka di PAUD Al-Muttaqin - Amat Hidayat; Neneng Antika; Marisatul Ummami (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Independent Curriculum requires Early Childhood Education (PAUD) teachers to develop the ability to design flexible, contextual, and child-centered learning through the development of Daily Lesson Plans (RPPH). However, in practice, teachers still experience difficulties in understanding the concept and implementation of RPPH based on the Independent Curriculum. This Community Service (PKM) activity aims to improve teachers' competency in developing RPPH through mentoring activities at Al-Muttaqin PAUD. The methods used were training, workshops, and intensive mentoring, actively involving teachers in the RPPH design process. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis employed a qualitative descriptive approach. The results of the activity showed an increase in teachers' understanding of the Independent Curriculum concept and their skills in developing RPPH that are more systematic, contextual, and appropriate to the characteristics of early childhood. Furthermore, teachers became more creative in developing child-centered learning activities. Thus, this mentoring activity was effective in improving the professionalism of PAUD teachers and the quality of lesson planning.